Pattern of Common Eye Diseases in Children Attending Outpatient Eye Department Khyber Teaching Hospital - Nasir Saeed, Naimatullah Khan Kundi, Sadia Sethi, Mohammad Junaid Sethi (Pakistan Journal of Ophthalmology, 2008)
Purpose: The objectives were to find out the pattern of eye diseases by age and sex and treatment given to them. Material and Methods: In this hospital based study all children coming to outpatient Department of Ophthalmology, Khyber Teaching Hospital Peshawar over a period of two weeks from 1st June 2007 to 14th June 2007 were examined. A total of 202 children in age of 0-16 were included in the study. Informed consent was taken from all the patients. A standard performa was filled in for recording personal history examination results and treatment required. Results: On average 20 children were examined daily. 60.8% were male, 39.1% were female. Vernal Keratoconjunctivitis was the most common disorder affecting 35.6% children followed by refractive errors involving 12.8% children. 39.6% of children attending eye outpatient were in age group 0-6 years, 46% were in age group 6-12 years while 14.3% were in age group 13-16 years. 59.2% children needed medical treatment, 28% required surgery while 12.8% required glasses. Conclusion: Vernal Catarrh in this study was the most common occurring disorder due to hot summers. Males were more affected than females. Most children needed medical treatment.